Correlation Between Fixed-Luminance Flicker Full-Field Electroretinogram Response and Macular Cone Density in Healthy Individuals - S. Saeed Mohammadi; Woong-Sun Yoo; Negin Yavari; Hassan Khojasteh Jafari; Christopher Or; Azadeh Mobasserian; Vahid Bazojoo; Amir Akhavanrezayat; Dalia El Feky; Osama Elaraby; Jia-Horung Hung; Cigdem Yasar; et al. (Life)
This is the studyto investigate the correlation between macular cone density (MCD) and flicker electroretinogram (ERG) response in healthy eyes. In this exploratory study, 23 eyes from 12 healthy subjects were enrolled in this study. The fixed-luminance flicker full-field electroretinogram (ffERG) responses of the retina and MCDs at 24 locations were measured using the Diopsys® NOVA™ system and the rtx1 adaptive optics retinal camera, respectively. Regression analysis was employed to evaluate the correlations. The mean age of the subjects was 30 ± 3 years. The average magnitudes of the flicker response and phase response were 13.44 ± 4.88 μV and 332.63 ± 22.12°, respectively. The MCDs for all 24 locations were 15,043 ± 3511 cones/mm². Among all locations, regression analysis revealed a significant correlation only at one specific location (0, −4°) between cone density and both the mean magnitude and phase of the flicker response, with p-values of 0.005 and 0.004, respectively.In conclusion, we identified a significant correlation between MCD and ffERG responses at a specific retinal locus (0, −4°). This finding may be attributed to the distribution of different cone types throughout the retina and the possibility that various cone types may contribute differently to ERG. Further studies are required to investigate this finding.